Clofarabine versus fludarabine‐based reduced‐intensity conditioning regimen prior to allogeneic transplantation in adults with AML/MDS. (17th October 2016) - Chevallier, Patrice; Labopin, Myriam; de La Tour, Regis Peffault; Lioure, Bruno; Bulabois, Claude‐Eric; Huynh, Anne; Blaise, Didier; Turlure, Pascal; Daguindau, Etienne; Maillard, Natacha; Yakoub‐Agha, Ibrahim; Guillerm, Gaelle; et al.
Abstract: We have retrospectively compared survivals between acute myeloid leukemia (AML)/myelodysplastic syndrome (MDS) patients who received either a clofarabine/busulfan (CloB2A2) or a fludarabine/busulfan (FB2A2) RIC regimen for allogeneic stem cell transplantation. Between 2009 and 2014, 355 allotransplanted cases were identified from the SFGM‐TC registry as having received either the FB2A2 ( n = 316, 56% males, median age: 59.2 years, AML 78.5%, first complete remission [CR1] 72%, median follow‐up: 20 months) or the CloB2A2 ( n = 39, 62% males, median age: 60.8 years, AML 62%, CR1 69%, median follow‐up: 22.4 months) RIC regimen. In multivariate analysis, FB2A2 was associated with significant lower overall survival (OS, HR: 2.14; 95%CI: 1.05–4.35, P = 0.04) and higher relapse incidence (RI, HR: 2.17; 95%CI: 1.02–4.61, P = 0.04) and a trend for lower leukemia‐free survival (LFS, HR: 1.75; 95%CI: 0.94–3.26, P = 0.08). These results were confirmed using a propensity score‐matching strategy. However, when considering AML and MDS patients separately, the benefit of the CLOB2A2 regimen was restricted to AML patients (2‐year OS FB2A2: 38% [14.5–61.6] vs. CloB2A2: 79.2% [62.9–95.4], P = 0.01; 2‐year LFS FB2A2: 38% [16–59.9] vs. CloB2A2: 70.8% [52.6–89], P = 0.03). The better survivals were due to the lower risk of relapse in this CloB2A2 AML subgroup (2‐year RI FB2A2: 41.2% [19–62.4] vs. CloB2A2: 16.7% [5–34.2], P = 0.05). This retrospective comparison suggests that the CloB2A2 RIC regimen can likely provide longer survival than that awarded by a FB2A2 RIC regimen and may become a new standard of care RIC regimen for allotransplanted AML patients. A prospective phase 3 randomized study is warranted. Abstract : CloB2A2 RIC regimen provided better OS and leukemia‐free survival compared to the standard FB2A2 RIC regimen in allografted acute myeloid leukemia (AML) patients. The better survivals observed in the CloB2A2 AML subgroup was due to a lower risk of relapse, confirming the higher antileukemic activity of clofarabine versus fludarabine.